Imaging endogenous opioid peptide release with [11C]carfentanil and [3H]diprenorphine: influence of agonist-induced internalization - Quelch, D; Katsouri, L; Nutt, D; Parker, C; Tyacke, R (SAGE Publications, 2014)
Understanding the cellular processes underpinning the changes in binding observed during positron emission tomography neurotransmitter release studies may aid translation of these methodologies to other neurotransmitter systems. We compared the sensitivities of opioid receptor radioligands, carfentanil, and diprenorphine, to amphetamine-induced endogenous opioid peptide (EOP) release and methadone administration in the rat. We also investigated whether agonist-induced internalization was involved in reductions in observed binding using subcellular fractionation and confocal microscopy. After radioligand administration, significant reductions in [(11)C]carfentanil, but not [(3)H]diprenorphine, uptake were observed after methadone and amphetamine pretreatment. Subcellular fractionation and in vitro radioligand binding studies showed that amphetamine pretreatment only decreased total [(11)C]carfentanil binding. In vitro saturation binding studies conducted in buffers representative of the internalization pathway suggested that μ-receptors are significantly less able to bind the radioligands in endosomal compared with extracellular compartments. Finally, a significant increase in μ-receptor-early endosome co-localization in the hypothalamus was observed after amphetamine and methadone treatment using double-labeling confocal microscopy, with no changes in δ- or κ-receptor co-localization. These data indicate carfentanil may be superior to diprenorphine when imaging EOP release in vivo, and that alterations in the ability to bind internalized receptors may be a predictor of ligand sensitivity to endogenous neurotransmitter release.